Pengawasan Distribusi Pupuk Bersubsidi pada KP3 (Komisi Pengawasan Pupuk dan Pestisida) Kabupaten Pangkep - Misrah, Misrah; Sudarmi, Sudarmi; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to determine the supervision of the distribution of subsidized fertilizers in KP3 (Commission for the Development of Fertilizers and Pesticides) in Pangkep Regency which focused on supervision techniques, namely direct supervision and indirect supervision, as well as knowing the factors that influenced the supervision of subsidized fertilizer distribution. This study used descriptive with a qualitative approach.  Data collection techniques used observation, documentation, and interviews. The results of this study showed that the surveillance  was still not going well and needed to be improved. The monitoring technique used  direct supervision which was not optimal because there were no measurement tools (standard), and indirect there were still many reports that were available on the issue of subsidized fertilizer. And the factors that influenced supervision were internal factors including human resources (HR) and financial resources (finance) which were minimal by only having 2 subsidized fertilizer supervisors. External inhibiting factors took the form of rejection in monitoring the distribution of subsidized fertilizers.